(untitled) - Tawney, R. H. (Honolulu, 1929)
This book introduce about the rural framework, the problem of the peasant, the possibilitiess of rural progess, the old industial order and the new.
Keywords: Công nghiệp,Agriculture,Industries,Nông nghgiệp; Trung Quốc,China,China,Trung Quốc